Institutional analysis of technical innovation: A review - Raymund Werle (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2011)
Different sub-disciplines of the social sciences analyse the evolution and diffusion of technical innovations from an institutional perspective. Important contributions are provided by socio-economic studies of national systems of innovation, by politico-economic research on the varieties of capitalism, and by the sociology of technology. These studies often start from rather simple distinctions between types of technical innovations (e.g., radical versus incremental) which they usually do not elaborate on. Such black-boxing of technology by and large facilitates detecting generalizable relations between institutional constellations and technical innovations. But a more sophisticated analysis of the relationship between institutions and technical innovations needs more precise concepts of both technology and institutions, and it must dismiss the prevailing institutional determinism. Processes of technical and institutional innovations are characterised by co-evolution, interaction and mutual adjustment. – – In verschiedenen sozialwissenschaftlichen Teildisziplinen wird die Entstehung und Ausbreitung technischer Innovationen aus einer institutionellen Perspektive analysiert. Wichtige Ansätze finden sich in der sozio-ökonomischen Forschung über nationale Innovationssysteme, der politökonomischen Forschung über die Spielarten des Kapitalismus und der Techniksoziologie. Die Arbeiten gehen oft von einfachen Unterscheidungen zwischen bestimmten Typen von technischen Innovationen (z.B. radikal versus inkrementell) aus, die sie in der Regel nicht sehr viel weiter entwickeln. Dieses black-boxing kann es erleichtern, generalisierbare Zusammenhänge zwischen institutionellen Konstellationen und technischen Innovationen aufzuzeigen. Das ist bisher aber auch deshalb nur selten gelungen, weil ein Defizit hinsichtlich der theoretischen Konzeptualisierung von institutionellen Arrangements besteht und gleichzeitig ein institutioneller Determinismus vorherrscht. Die Analyse von Wechselwirkungen zwischen technischen und institutionellen Neuerungen als Prozessen der Koevolution, Interaktion und wechselseitiger Anpassung könnte Abhilfe schaffen.
Keywords: 300